Kemauan Membayar dan Surplus Konsumen untuk Kemudahan Layanan Air Bersih pada Masyarakat Kembangbahu Menggunakan Contingent Valuation Method (Studi Kasus Dampak Kekeringan Pada Ketersediaan Air Bersih) - Marpaung, Ridwan (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2013)
Dryness occurred every year in Kembangbahu district brings impacts to water scarcity because Kembangbahu communities rely to rainfall to satisfy their water demand. To overcome this condition , they build some small lakes or reservoirs to attempt to collect rain water during dry season, but either way making water and also the water does not met health requirements. Therefore Kembangbahu societies need convenience clean water service. This study aims to analysis the Willingness to Pay and its consumers surplus for convinience of clean water service. Sample collected using simple random method of 49 respondents by interview and questioners. Analysis using Contingent Valuation Method (CVM) showed that, the predictor variabels like Bidding, and Income are influence significantly to Willingness to Pay for convinience of clean water service, with α=0,05, otherwise Education, Distance to Water Resource, Age, Water Consumption are not significantly influence to Willingness to Pay. By using regresion logistic to a household respondents showed that the mean Willingness to Pay is Rp.9.123 per jerigen (35 litre),and consumer surplus is Rp 7.123. Consumer surplus for all Kembangbahu communities with 2.617 population is Rp. 7.241.292. By known the variabels that influence to Willingness to Pay, and amount of consumer surplus, the expectation is that decision makers may improve for convinience of clean water service in Kembangbahu communities.